Management of International Distribution Channels, Case L-Fashion Group Ltd: Analysis of Channel Leading through Channel Partners - Yrjälä , Tiia (My University, 2007)
Distribution channels create a competitive advantage for companies if channels and relationships are managed successfully. However, it appears that not all the companies realize the value of distribution partnerships and therefore partnerships are managed poorly. In consequence, the performance of distribution channels is not efficient. The object of the study was to analyze the role of distribution partnerships in order to understand partnerships’ position in undivided management process of the channels. The role of partnerships was analyzed in the context of channel design, segmentation and positioning phases. These were some of the findings in which the partnerships actuated. The dynamics of partnerships were brought out in order to survey closer the elements that influence on channel leading and on the behaviour inside the channel. The research was done through case study method. Previous theories of the topic were used as a mirror to compare empiric results. The qualitative research was accomplished via theme interviews of the specialists who manage the case company’s international distribution channels. The main findings of the study emphasised that in fashion-apparel industry the role of partnerships in channel management is marked in two-phase segmentation process and in positioning decisions. According to the study, through channel partnerships and retailer response it is conceivable to increase channel efficiency. The study suggests that the growing power of retailers and shortened but integrated channels create challenges to develop partnerships and channel performance further.
Keywords: International distribution channel; partnerships; dynamics; channel management; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|